(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The rise of antimicrobial resistance poses a global health challenge, driven by the widespread misuse of antibiotics. This misuse includes self-medication, sharing of antibiotics and failing to complete prescribed courses. This fosters an environment conducive for antibiotic resistance making future treatment less effective. Objectives: This study aims to evaluate the knowledge, attitudes, and practices (KAP) of antibiotic use/misuse and their influencing factors among pharmacy clients in Ogun State, Nigeria. Methods: A descriptive cross-sectional study was carried out in ten (10) community pharmacies obtained from the list provided by the Association of Community Pharmacists of Nigeria, Ogun State branch, across its five zones in Ogun State, Nigeria. Pre-tested questionnaires adapted from previous studies were used to collect data which was entered into Microsoft Excel 2016 and analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. Descriptive and inferential statistical analyses were carried out with significance level set at ≤0.05. Results: Good knowledge and practice (KP) scores of pharmacy clients about antibiotic use of 54.5% and 56.2% but poor attitude to antibiotics (60.5%) was documented along with notable misconceptions. Several demographic factors influenced the KP levels including gender (p=0.00027), marital status (p=0.013), religion (p=0.005), and education (p=0.001) for knowledge; and religion (p=0.027) and education (p=0.006) for practices. Conclusion: The study showed that though moderate levels of KP were obtained, there is a need for targeted interventions to improve public awareness about antibiotics and promote responsible use.